The effect of healthcare data analytics training on knowledge management: A quasi-experimental field study - Byeong Jo Kim; Maria Tomprou (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
This study aims to provide practice-oriented evidence regarding the implementation of healthcare data analytics and its impact on the use of new data analytics tools and relevant analytical skills improvement. A quasi-experimental pre-test/post-test controlled study was conducted in a large medical system in the eastern United States. Healthcare data analytics training program participants (N = 21) and a comparison group comprising trainee-identified peers completing comparable work (N = 27) were compared at the start of training and one year later. Results showed that both trainees and peers demonstrated improved healthcare data analytics skills over time, related to concomitant increases in their healthcare data analytics-related learning and performance goals. This study suggests that healthcare organizations aiming at successfully implementing a new data analytics infrastructure should provide well-designed training that enables trainees to develop specific learning and performance goals as well as improve relevant skills and ability to use new tools.
Keywords: 650; healthcare data analytics; leader vision; learning goals; performance goals; quasi-experimental study; training